Occupational and locational substitution: measuring the effect of occupational and regional mobility - Alisher Aldashev (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The paper analyzes effects of occupational and regional mobility on the matching rate using the monthly panel disaggregated on regional and occupational level. The main contribution of the paper is measuring the effect of substitutability between vacancies for different occupations and vacancies in different regions on matchings. The estimates indicate higher regional mobility in West Germany but higher occupational mobility in East Germany. The results show that if occupations were perfect substitutes, the number of matches could increase by 5-9%. Perfect regional mobility could increase matchings by 5-15%. It is also shown that partial aggregation causes a downward bias in substitutability estimates.
Keywords: J62; J63; R23; J61; 330; Matching function; constant elasticity of substitution; spatial correlation; occupational and regional mobility; nonlinear least squares; GMM; Arbeitsmobilität; Regionale Arbeitsmobilität; Beruf; Faktorsubstitution; Matching; Deutschland; Alte Bundesländer; Neue Bundesländer